THE INFLUENCE OF PRODUCT QUALITY, COSTS, AND DISTRIBUTION ON THE INCOME OF PORANG FARMERS - Sefnat Aristarkus Tang (International Journal of Multidisciplinary Research and Literature, 2022)
This study aims to determine the effect of product quality, cost, and distribution on the income of porang farmers in Kuifana Village, District South Century Alor Regency. The population in this study was all porang farmers with a sample of 30 people. And the Data collection uses questionnaires and data processing using multiple linear regression. The results showed that the significance value of the t-test of the product quality variable was 0.016, the cost variable was 0.000, and the distribution variable was 0.031. When compared with the alpha value, the t-test value of each independent variable is smaller than the alpha value (α=0.05) so that partially the product, cost, and distribution variables have a significant positive effect on the income variable. While simultaneously, the significance value of the F test is 0.000, where this value is smaller than the alpha value (α = 0.05). Simultaneously, all independent variables have a significant positive effect on the dependent variable